Technical Approach in Table Tennis Training: A Literature Analysis - Sagala, Ramlan Sahputera; Daulay, Dicky Edwar; Samudra, Bayu; Januarto, Abdu Yudha; Lubis, Irwansyah Hafidh; Telaumbanua, Imam Fauzi; Simbolon, Dicky Bastian (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This study conducts a literature analysis on the technical approach in table tennis training with the aim of providing comprehensive insights for coaches, sports experts, and policymakers. Through searching and selecting relevant articles, we identified traditional approaches, modern approaches integrating biomechanical analysis, and relevant psychological approaches in the literature. The results of this literature review provide a deep understanding of the strengths and weaknesses of each approach as well as their practical implications in table tennis training. The integration of these approaches offers a holistic approach that can enhance the quality of table tennis training, especially in the context of Indonesian sports.